PSVI-6 Thresholds of Outdoor Temperatures on Fertility Measures of Different Parity Sows in Spanish Herds. (7th May 2021) - Iida, Ryosuke; Piñeiro, Carlos; Koketsu, Yuzo
Abstract: High temperature is one of the environmental factors which impair sow fertility such as weaning-to-first-mating interval (WMI) and farrowing rate especially in parity 1 sows. The objective of this study was to explore thresholds of temperature damaging fertility in different parity sows. Data of sows serviced from 2011 to 2016 in 142 herds were coordinated with daily maximum temperature (Tmax) from 31 weather stations close to the herds. A two-stage approach was used to determine the best fit model. In the first stage, means and their variance-covariance matrix in each degree Celsius were estimated by a mixed model. Then, piecewise models with a different breakpoint were fitted to the estimates by generalized least squares. Medians of WMI in parity 1 and 2 or higher sows were 5 and 4 days, respectively. Farrowing rates in different parity sows were 85.0–88.7%. The thresholds of mean Tmax during lactation leading to a prolonged WMI were 16 and 23–25°C for parity 1 and 2 higher sows, respectively. The 10°C increase in Tmax from the thresholds delayed WMI in parity 1 and 2 or higher sows by 0.62 and 0.46–0.49 days, respectively (P < 0.01). Meanwhile, the thresholds of mean Tmax from 21 to 14 days before service leading to reductions in farrowing rate were 21, 19 and 21–22°C for parity 0, 1 and 2 or higher sows, respectively. As the Tmax increased by 10°C from the thresholds, farrowing rate in parity 0–1 and 2 or higher sows decreased by 2.9 and 2.2–2.6%, respectively (P < 0.01). Lactating sows in parity 1 suffered from heat stress at a relatively low outdoor temperature. This implies that the temperature is warmer in lactating barns than in outdoor. We recommend changing thermostat set at barns in spring from those in winter in order to increase ventilation rates earlier.